„Kronika Podhorecka” jako źródło do badań nad dziejami zamku w Podhorcach w drugiej połowie XIX wieku na początku XX wieku (Krakowskie Pismo Kresowe, 2020)
“Kronika Podhorecka” as a Primary Source for the History of the Pidhirtsi Castle in the Second half of the 19th Century and at the Beginning of the 20th Century„Kronika Podhorecka” has been preserved in two versions: the first working version was written by A. Kryczynski (1869-1887) and the second one was completed by the next castle administrators (1869-1906). This article aims to analyze this primary source of the history of the Pidhirtsi castle and its owners: the time of its composition, its goal, the role of castle administrators in the history of Pidhirtsi castle. The article contains an edition of “Kronika Podhorecka”, reconstructed on the basis of the archival source.